Direct Vertebral Artery Access for Coil Embolization of a Partially Thrombosed Mid-Basilar Trunk Aneurysm: Technical Limitations. Issue 4 (16th June 2021) - Miller, Charles A; Felbaum, Daniel R; Liu, Ai-Hsi; Mai, Jeffrey; Alfawaz, Abdullah; Lynes, John; Armonda, Rocco
Abstract: BACKGROUND AND IMPORTANCE: Partially thrombosed basilar aneurysms have a high morbidity from the rupture risk and mass effect prompting early treatment. Depending on the size and location, they pose a surgical challenge often requiring multiple endovascular treatment modalities. Here we present a partially thrombosed mid-basilar aneurysm successfully coil embolized with direct vertebral artery access and discuss the technical limitations of direct V1 access. CLINICAL PRESENTATION: A 70-yr-old woman presented with acute onset headache, nausea, and vomiting. A computed tomography (CT) head demonstrated a hyperdense prepontine mass which was further characterized as a partially thrombosed basilar aneurysm on CT angiography. After multiple failed attempts to access the vertebral artery via femoral and radial access the patient was taken to the operating room (OR) for surgical exposure of the right V1 segment and direct cannulation of the vertebral artery. The aneurysm was successfully coiled and the vertebral artery closed primarily. The patient was discharged home without any neurological deficits. CONCLUSION: Partially thrombosed mid-basilar aneurysms are difficult to treat both surgically and endovascularly. We present a case where endovascular access to the aneurysm was very challenging requiring direct exposure and cannulation of the V1 segment to successfully embolize with coils and discuss the technical limitations of this approach.